Structural Parameter Sensitivity Analysis of an Aircraft Anti-Icing Cavity Based on Thermal Efficiency - Feng Zhang; Yang Gao; Huiju Yao; Yameng Wang; Kailiang Luo (International Journal of Aerospace Engineering)
The objective of this paper is to accurately describe the influence of structural parameter uncertainties on the thermal efficiency of an aircraft wing anti-icing cavity. To do this, a new method of parameter sensitivity evaluation is proposed according to the weighted stochastic response surface method. First, the concept of fitting the explicit performance function of the anti-icing cavity structure using the weighted stochastic response surface method is presented. A structural parameter sensitivity analysis based on thermal efficiency is then conducted considering the uncertainties of the position of the flute tube, the height of the double-skin channel, and the diameter and angle of the jet holes. The results indicate that the height of the double-skin channel and the diameter of the jet holes are the main factors influencing the functional reliability of the anti-icing cavity.